Content of Music Education in Higher Education: From Interdisciplinarity to Transdisciplinarity - Oleksiuk, Olga (Музичне мистецтво в освітологічному дискурсі, 2025)
The relevance of all processes in the field of music education considers its content modernization from different points of view. The criteria and signs of modernization in the content of music education are characterized as improvement, renewal, imitation, continuity and a specific transition in terms of the principles and methods of its implementation and provision. Accordingly, the priority is the change in the requirements of time and the process of transition from the traditional view of education to innovative approaches, as well as its continuity and combination with valuable national traditions. The modernization of music education is aimed at improving the quality and integrity of the system through transformations and its ability to authoritatively respond to the challenges of the 21st century. The basis for modernization of the music education content is the integration of modern technologies and scientific knowledge, primarily in the field of musical art and pedagogy, humanities and natural sciences. The task of the above-mentioned areas is to form a holistic view of a person, a logical transition to a personality-centered approach, the integrative nature of the latest technologies, development and self-development, ensuring the process of creativity of students to prepare them for the realities of the modern socio-cultural space. This approach focuses on both professional and general cultural needs through the objective expansion of all types of professional activity and the use of innovative teaching methods. An important category is «integrity» as a measure of spirituality, humanity, personal and creative purpose of education. The content of modern music education also includes individual values, which are learned through integrated specialized academic disciplines aimed at helping future specialists navigate the specifics of the development of an individual’s creative potential. This process is provided on an acmeological basis in order to formulate conceptual theoretical and methodological positions aimed at preserving and increasing spiritual and ideological values, national traditions, and most importantly, the continuity of scientific and pedagogical schools. Актуальність всіх процесів у сфері музичної освіти розглядає модернізацію її змісту з різних точок зору. Критерії та ознаки модернізації у зміст музичної освіти характеризуються як удосконалення, оновлення, наслідування, спадкоємність та конкретний перехід щодо принципів і методів її впровадження і забезпечення. Відповідно пріоритетними постають зміна щодо вимог часу та процесу переходу від традиційного погляду на освіту до інноваційних підходів, а також її бехперервності і поєднання із ціннісними національними традиціями. Головна мета модернізації музичної освіти спрямована на підвищення якості й цілісності системи шляхом трансформацій та її здатності авторитетно реагувати на виклики XXI століття. Базовою основою модернізації змісту музичної освіти є інтеграція сучасних технологій і наукових знань, передусім, в галузі музичного мистецтва і педагогіки, гуманітарних та природничих наук. Завдання вищезазначених напрямків полягає у формуванні цілісного уявлення про людину, логічний перехід до особистісно-орієнтованого підходу, інтегративність новітніх технологій, розвиток і саморозвиток, забезпечення процесу креативності студентів з метою підготовки до реалій сучасного соціокультурного простору. Такий підхід концентрує увагу як на фахових, так і на загальнокультурних потребах шляхом об’єктивного розширення всіх видів професійної діяльності та використання інноваційних методик навчання. Важливою категорією постає «цілісність» як міра духовності, людяності, особистісного і творчого призначення освіти. Зміст сучасної музичної освіти включає також окремі цінності, які засвоюються через інтегровані спеціалізовані навчальні дисципліни, спрямовані на те, щоб допомогти майбутнім фахівцям зорієнтуватися в специфіці розвитку творчого потенціалу особистості. Цей процес забезпечується на акмеологічній основі з метою сформулювати концептуальні теоретико-методологічні позиції, які спрямовані на збереження та примноження духовних і світоглядних цінностей, національних традицій, а головне – і спадкоємності науково-педагогічних шкіл.